Level of Knowledge, Apprehension and Readiness of Food Waste Segregation in the Cafeterias - S. A. Rahman, N.; A. Zahidi, S.; M. Zain, S.; E. A. Basri, N (International Journal of Engineering and Technology, 2019)
In recent years, increased in food waste generation has affected the environment due to the lack of awareness among consumers. A need for assessment by surveying was performed at UKM Bangi campus to determine the level of knowledge, apprehension, and readiness in food waste segregation aspect in the cafeteria among residents. The survey result will determine whether sustainable cafeteria programme should be implemented to increase awareness.Â The questionnaire was designed as a tool to collect data from 300 residents in UKM Bangi campus. The collected data was analysed using the Rasch model and Predictive Analytics SoftWare (PASW). Results of the assessment show that most of the residents have more knowledge on hygiene in the cafeteria associated with waste management instead of having concern and willingness to separate food wastes in the cafeteria as a way of managing wastes properly. As a conclusion, sustainable cafeteria programme should be executed to increase the level of readiness and apprehension of residents towards food waste segregation in the cafeteria.Â Â